2015
DOI: 10.1161/strokeaha.115.010250
|View full text |Cite
|
Sign up to set email alerts
|

Younger Stroke Patients With Large Pretreatment Diffusion-Weighted Imaging Lesions May Benefit From Endovascular Treatment

Abstract: Background and Purpose— Lesion volume on diffusion-weighted magnetic resonance imaging (DWI) before acute stroke therapy is a predictor of outcome. Therefore, patients with large volumes are often excluded from therapy. The aim of this study was to analyze the impact of endovascular treatment in patients with large DWI lesion volumes (>70 mL). Methods— Three hundred seventy-two patients with middle cerebral or internal carotid artery occlusions exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 46 publications
8
81
1
2
Order By: Relevance
“…This is consistent with the few studies that reported on the outcome of patients treated despite large initial DWI lesions. Thus, Gilgen et al 17 reported that 21% of 66 such patients had favorable outcome, in accordance with the one in 6 with favorable outcome in the Diffusion and Perfusion Imaging Evaluation for Understanding Stroke Evolution (DEFUSE) study. 8 A second and even more important finding from our study is that recanalization was associated with favorable outcome in patients with DWI≥70 mL.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This is consistent with the few studies that reported on the outcome of patients treated despite large initial DWI lesions. Thus, Gilgen et al 17 reported that 21% of 66 such patients had favorable outcome, in accordance with the one in 6 with favorable outcome in the Diffusion and Perfusion Imaging Evaluation for Understanding Stroke Evolution (DEFUSE) study. 8 A second and even more important finding from our study is that recanalization was associated with favorable outcome in patients with DWI≥70 mL.…”
Section: Discussionsupporting
confidence: 53%
“…Two hundred and six were excluded because of bridging therapy (n=32), inclusion in a neuroprotection study (n=4), non-middle cerebral artery stroke (n=53), baseline evaluation with CT only (n=36), initial MRI not available in Digital and Communications in Medicine (DICOM) format (n=16), no visible initial occlusion (n=42), no data on recanalization (n=9), or 90-day modified Rankin scale score not available (n=14). Of note, the latter 14 patients had similar NIHSS at 24 hours than the included patients (median 9 [interquartile range 6-14] versus 11 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]; P=0.72). Excluded patients did not differ from the included patients for age or onset-to-MRI time, but had lower baseline NIHSS (median 10 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] versus 15 [9][10][11][12][13][14][15][16][17][18][19][20]; P<0.0001).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, we did demonstrate with others that some patients with large infarction defining a malignant profile with a DWI lesion volume of >70 mL may still benefit from an emergent revascularization within 6 hours. [8][9][10] With this as a background, we aim to investigate first the characteristics of IGR in a cohort of consecutive patients experiencing an acute BI downstream of a proximal ICA term/M1 occlusion treated by endovascular treatment within 6 hours after onset and imaged by MR-DWI before treatment, and second its impact on the rate of favorable outcome according to the occurrence of a successful recanalization. …”
mentioning
confidence: 99%
“…Eins og staðan er í dag hefur reynst erfitt að skilgreina hóp sjúklinga sem ekki hefur gagn af segabrottnámi. 44,45 Gera þarf frekari framskyggnar rannsóknir, þar sem flestar rannsóknir útilokuðu sjúklinga með stór óaft-urkraef drep. Íhuga aetti segabrottnám hjá sjúklingum með stórt kjarnadrep og hjá sjúklingum sem koma inn nokkrum klukkustundum frá upphafi einkenna.…”
Section: Er Nauðsynlegt Að Gera Frekari Myndrannsóknir En Ts Og Ts-aeunclassified